Effect of material and geometry on crushing behaviour of laminated conical composite shells - Mahdi, E.; Hamouda, A.M.S.; Sahari, B.B.; Khalid, Y.A. (Kluwer Academic Publishers, 2002)
This paper examines the effects of the material and structural geometry on the crushing behaviour, energy absorption, failure mechanism and failure mode of circular conical composite shell. The static crushing behaviour of circular conical composite shell under uniform axial compressive load has been investigated experimentally. The cone vertex angles used were 0, 6, 12 and 18 degrees. The cone vertical length and bottom outer diameter were kept for all the cases as 100 and 110 mm, respectively. Failure modes were examined using several photographs taken during the crushing stages for each specimen. Results obtained from this investigation showed that the initial failure was dominated by the interfacial and shear failure, while the delamination and eventually fibre fracture were dominated the failure mechanism after the initial failure. It has also found that the static crushing behaviour of the circular conical shell is very sensitive to the change in the vertex angle. Reinforcement type greatly affects the energy absorption of the circular conical and cylindrical shells.